Unconscious mental life and reality - Ekins, Richard, 1945- (Karnac, 2002)
It is the aim of the present collection of seminal essays to offer a balanced yet rigorous examination of the durability and contemporary relevance of psychoanalysis, understood as a comprehensive system of theory and technique. The contributors eschew the establishment of yet another school of Freudian thought, not wishing to add to the already confusing array of competing and conflicting perspectives. 159 pages.